The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12325-018-0758-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rheumatoid Arthritis with Certolizumab Pegol: Results from PROACTIVE, a Non-Interventional Study in the UK and Ireland

Abstract: IntroductionThe objective of this non-interventional study was to investigate the long-term safety and effectiveness of certolizumab pegol (CZP) in patients with rheumatoid arthritis (RA) in the UK and Ireland.MethodsPatients were prescribed CZP at their physicians’ discretion and followed during routine clinical practice for up to 88 weeks. DAS28(ESR) response (defined as at least a 1.2-point reduction from baseline) was measured in the full analysis set (FAS) at week 12, and patients were categorized by week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…17 While, the PROACTIVE non-interventional study in the United Kingdom and Ireland had a higher retention rate, with 68.5% of patients completing the study to Week 88. 18 Within the present study, it was observed that similar proportions of patients achieved DAS28 < 2.6 at Week 104, whether they had <2 years or ⩾2 years RA duration. Greater improvements in disease activity (DAS28) were observed in anti-TNF-naïve patients, when compared to patients with prior anti-TNF experience.…”
Section: Discussionsupporting
confidence: 68%
“…17 While, the PROACTIVE non-interventional study in the United Kingdom and Ireland had a higher retention rate, with 68.5% of patients completing the study to Week 88. 18 Within the present study, it was observed that similar proportions of patients achieved DAS28 < 2.6 at Week 104, whether they had <2 years or ⩾2 years RA duration. Greater improvements in disease activity (DAS28) were observed in anti-TNF-naïve patients, when compared to patients with prior anti-TNF experience.…”
Section: Discussionsupporting
confidence: 68%
“…The majority of patients achieved a EULAR response within 12 months (75.3%), which was sustained to 36 months among patients still in the study. Similar improvements in disease activity have been observed in previous observational studies into the long-term effec-tiveness of CZP (11)(12)(13). However, the EULAR response rate in ECLAIR was lower compared to the RAPID 1 study (96.2% at 12 months), which is likely due to higher baseline disease activity in the latter.…”
Section: Safetysupporting
confidence: 80%
“…Long-term observational data in more representative populations are therefore necessary, and are frequently considered or requested by health authorities. Several observational studies have previously reported on the effectiveness and safety of CZP in real-world settings in Canada, Germany and the UK, but an observational study of an anti-TNF has yet to be conducted in France (11)(12)(13). To this end, the French National Authority for Health requested an observational study to assess the effectiveness and safety of CZP up to 36 months in patients with moderate-to-severe RA in a real-world setting in France.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a study by Keystone et al [ 5 ] predicted the 52-week response of CZP after three injections. Due to the different dosing schedules, concomitant medications, and other confounding factors, prediction of the time point of the long-term treatment response to different bDMARDs is expected to vary [ 6 ]. Studies have also found that CZP provided rapid and sustained clinical improvement in RA patients regardless of prior TNFi use [ 7 ].…”
mentioning
confidence: 99%